INVESTIGATION OF REFUELING STATIONS INFLUENCE ON URBANIZED ENVIRONMENT WITH THE HELP OF PRECIPITATION BIOTESTING - Bilyk, Tetiana I.; Shtyka, Olga S. (Proceedings of National Aviation University (archive), 2009)
The problem of refueling stations construction within residential districts of a city is currently the object of considerable attention in present publication. Results of atmospheric precipitation biotesting taken on the territory of refueling stations within the residential districts and beyond the city were analyzed.